Research on the influence of curtain grouting parameters on the stability of tunnel surrounding rock and lining structure under the action of local high water pressure - Lianhui Li; Zonglong Zhang; Changyong Nie; Xuebing Hu; Zongzhi Li; Liang Cheng; Wenfeng Zhang (AIP Advances)
Choosing the reasonable and economical grouting parameters is crucial for controlling the seepage field of surrounding rock and tunnel stability. This paper adopted the fluid–solid coupling theory based on FLAC3D to establish numerous simulations on the stability of surrounding rock and lining structure in karst tunnels under the different grouting conditions. The influences of grouting layer thicknesses and their permeability coefficients on the mechanical behaviors of lining structure, seepage, and stress properties of surrounding rock were investigated. The results show that with the increase of grouting thickness and its ratio of permeability, the maximum flow velocity and flow rate per liner meter in surrounding rock, the bending moments and axial forces, and the horizontal and vertical displacements of the lining structure all exponentially decrease, but safety factors at different positions of the lining structure first rapidly and then slowly increase. The changes in safety factor and uplift displacement at the inverted arch are more significant, and the minimum safety factor occurs at the left arch foot. As the grouting thickness and its ratio of permeability increase, the plastic zone range in surrounding rock decreases and expands, respectively. Through considering the improvement effect and economy of grouting comprehensively, choosing a grouting layer thickness of 7–9 m and a ratio of permeability of 20–50 is an ideal configuration parameter to ensure the stability and safety of karst tunnels under the conditions of this paper. The research results could provide references for choosing the reasonable grouting parameters in karst tunnels.